Exploring Silyl Protecting Groups for the Synthesis of Carbon Nanohoops - Kręcijasz, Remigiusz B.; Malinčík, Juraj; Šolomek, Tomáš (Synthesis, 2023)
The synthesis of topological molecular nanocarbons, such as hoop-like [n]cycloparaphenylenes, requires the use of spatially prearranged, pro-aromatic units to overcome a build-up of large molecular strain in their curved structures. The used cyclohexadienyl units, however, contain tertiary alcohols that need protection to prevent side reactions until the aromatization step that affords the final curved hydrocarbon. Although alkyl and triethylsilyl groups have been successfully applied as protecting groups for this purpose, each suffers from specific drawbacks. Here, we explore the potential of sterically more crowded silyl groups, namely, tert-butyldimethylsilyl and triisopropylsilyl, as alternatives to the established protection strategies. We show that tert-butyldimethylsilyl can be easily installed and removed under mild conditions, displaying markedly higher resistance towards acids or bases than the triethylsilyl group used to date. Unlike in the case of alkyl groups, tert-butyldimethylsilyl also preserves a high stereoselectivity during the nucleophilic additions of ArLi. Furthermore, we demonstrate that both tert-butyldimethylsilyl and triethylsilyl groups can be installed on the same substrate, and that the latter be selectively deprotected. Thus, the high stereoselectivity, improved stability, and easy deprotection make tert-butyldimethylsilyl an excellent protecting group for the synthesis of carbon nanohoops.
Keywords: topological molecular nanocarbons; carbon nanohoops; cycloparaphenylenes; protecting groups; silyl ethers; tert-butyldimethylsilyl; macrocycles; orthogonality